Pengembangan LKPD Berbasis Inkuiri Terbimbing untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SMA pada Materi Sistem Ekskresi - Haryani, Putri; Khairuna, Khairuna; Adlini, Miza Nina (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This study aims to develop instructional media in the form of guided inquiry-based LKPD on excretion system material to test the feasibility, practicality and determine the effectiveness of LKPD. This research used R&D research methods with the Borg & Gall development model (research and information collecting, planning, develop preliminary form of product, preliminary field testing, main product revision, main field testing and operational product). The test subjects in this study were students of class XI SMA Negeri 1 Brandan Barat. The media expert validation results obtained an average percentage of 92.5% with a very decent category. The results of the material expert validation obtained an average percentage of 93.75% with a very decent category. The results of the teacher’s response assessment obtained an average percentage of 91% in the very practical category. The results of the assessment of student responses in the limited scale trials obtained an average percentage of 80.99% in the very practical category and in the large scale trials and average percentage of 83.99% was obtained in the very practical category. Based on the results of the feasibility, practicality and product effectiveness tests, the guided inquiry-based LKPD on excretion system material develop is feasible, practical and effective for improving students critical thinking skills. Keywords: LKPD; Guided Inquiry; Critical Thinking; Borg & Gall Model R&D; Excretion System